Vav synergizes with protein kinase CΘ to mediate IL-4 gene expression in response to CD28 costimulation in T cells - Hehner, Steffen Peter; Li-Weber, Min; Dröge, Wulf; Krammer, Peter H. (The journal of immunology, 2000)
The secretion of IL-4, which displays many important immunoregulatory functions, is restricted to cells of the Th2 subtype. In this study, we investigated the early signaling events leading to the activation of IL-4 transcription. Vav, the protein kinase C (PKC) isoform Θ, and the adaptor protein SLP76 (SH2-domain-containing leukocyte protein of 76 kDa), induced transcription from the IL-4 promoter. Vav and PKCΘ synergistically activated human IL-4 promoter transcription and IL-4 mRNA production and were found to be constitutively associated in vivo. CD3/CD28-induced IL-4 transcription was inhibited upon coexpression of dominant negative forms of Vav, the adaptor proteins LAT (linker for activation of T cells) and SLP76, PKCΘ, and components of the pathways leading to the activation of c-Jun N-terminal kinase (mitogen-activated protein kinase kinase 7 (MKK7), mixed lineage kinase 3 (MLK3)) and NF-κB (IκB kinase α and IκB kinase β). The Vav/PKCΘ-mediated synergistic activation of IL-4 transcription was not inhibited by cyclosporin A. Three independent experimental approaches revealed that Vav/PKCΘ-derived signals selectively target the P1 and positive regulatory element (PRE)-I elements contained within the human IL-4 promoter. Vav/PKCΘ strongly activated a luciferase reporter construct controlled by trimerized P1 or PRE-I elements and furthermore stimulated DNA binding of nuclear proteins to the P1 and PRE-I elements. Vav/PKCΘ-induced transcription from the IL-4 promoter was almost completely abrogated by mutation of either the P1 or the PRE-I element within the entire IL-4 promoter.